2020
DOI: 10.3390/su12125073
|View full text |Cite
|
Sign up to set email alerts
|

The Ripple Effect and Spatiotemporal Dynamics of Intra-Urban Housing Prices at the Submarket Level in Shanghai, China

Abstract: The ripple effect of housing price movements between cities has been extensively investigated, but there are relatively few studies on this topic within a metropolitan context, especially at the submarket level. This paper describes the use of ripple effect theory to examine the diffusion process and convergence of intra-urban housing prices at the submarket level in Shanghai, an emerging global city in China. The analysis is based on directed acyclic graphs, local indicators of spatial association time-paths,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 85 publications
0
8
0
Order By: Relevance
“…The empirical research to date in this area is not very extensive, and to the best of the author's knowledge only several such analyses have been developed. In particular, studies on the presence of convergence clubs in the residential market have been conducted in the USA (Kim and Rous 2012 ; Apergis and Payne 2012 , 2019 , 2020 ; Montañés and Olmos 2013 ), China (Meng et al 2015 ; Lin et al 2015 ; Zhang et al 2017 ; Hu et al 2020 ), the UK (Montagnoli and Nagayasu 2015 ; Holmes et al 2019 ), Spain (Blanco et al 2016 ), Australia (Awaworyi Churchill et al 2018 ), South Africa (Apergis et al 2015 ) and Poland (Matysiak and Olszewski 2019 ; Tomal 2019a , 2020a ). It should be noted that almost all of the above studies analysed the convergence of sales prices in the residential market.…”
Section: Introductionmentioning
confidence: 99%
“…The empirical research to date in this area is not very extensive, and to the best of the author's knowledge only several such analyses have been developed. In particular, studies on the presence of convergence clubs in the residential market have been conducted in the USA (Kim and Rous 2012 ; Apergis and Payne 2012 , 2019 , 2020 ; Montañés and Olmos 2013 ), China (Meng et al 2015 ; Lin et al 2015 ; Zhang et al 2017 ; Hu et al 2020 ), the UK (Montagnoli and Nagayasu 2015 ; Holmes et al 2019 ), Spain (Blanco et al 2016 ), Australia (Awaworyi Churchill et al 2018 ), South Africa (Apergis et al 2015 ) and Poland (Matysiak and Olszewski 2019 ; Tomal 2019a , 2020a ). It should be noted that almost all of the above studies analysed the convergence of sales prices in the residential market.…”
Section: Introductionmentioning
confidence: 99%
“…Second, differently from the previous studies that demonstrated monocentricity for spillover effects of regional housing prices [67,68], a polycentric structure of the network was observed, and central cities in each urban agglomeration were identified by the block model analysis. Plus, the impulse responses on other cities' housing prices caused by central cities showed different characteristics in terms of intensity and breadth, but all persisted in the lag period.…”
Section: Discussionmentioning
confidence: 66%
“…Teye and Ahelegbey (2017) incorporate the DAG into the Bayesian vector auto-regressive framework (Ahelegbey et al , 2016) to explore spatio-temporal relations among housing prices in twelve provinces of The Netherlands and find that Noord-Holland was most predominant during 1995Q1–2005Q2 while Drenthe became most central during 2005Q3–2016Q1. Hu et al (2020) use the DAG to analyze the diffusion process of intra-urban housing prices at the sub-market level in Shanghai, China and find that geographical and economic proximities contribute to the process. They also determine a complex recursive process of price spillovers from high- to low-priced sub-markets and vice versa, which contributes to spiraling local housing prices.…”
Section: Literature Reviewmentioning
confidence: 99%